General versus pain‐specific cognitions: Pain catastrophizing but not optimism influences conditioned pain modulation. (28th August 2018) - Traxler, Juliane; Hanssen, Marjolein M.; Lautenbacher, Stefan; Ottawa, Fabian; Peters, Madelon L.
Abstract: Background: Previous studies found evidence that dispositional optimism is related to lower pain sensitivity. Recent findings suggest that temporarily increasing optimism by means of imagining a positive future may also have pain‐alleviating effects. Objectives: The present experiment was designed to investigate conditioned pain modulation (CPM) as a potential underlying mechanism of this pain‐alleviating effect of induced optimism. Methods: For this purpose, 45 healthy participants were randomized into an optimistic or neutral imagery condition. Additionally, participants completed questionnaires on dispositional optimism, pain catastrophizing and pain expectations. CPM was assessed by delivering a series of five heat pain stimuli on the nondominant hand before and during immersion of the dominant hand in water of 5°C for 70 s. Results: A clear CPM effect was found, that is heat pain reports were lower during simultaneous cold water stimulation. Although the optimism manipulation successfully increased optimism, it did not affect pain ratings or CPM. Post hoc analyses indicated that dispositional optimism was not associated with the magnitude of CPM, but pain catastrophizing and pain expectations did significantly correlate with the CPM effect. Conclusion: Pain‐specific but not general cognitions appear to influence endogenous pain modulation. Significance: Conditioned pain modulation is not the underlying mechanism of the pain‐alleviating effects of induced optimism. However, pain‐specific cognitions including pain catastrophizing and pain expectations affect endogenous pain modulation which should be taken into account in treatment and CPM research.